Analysing Student Participation in the Life and Governance of Hungarian Higher Education Institutions: A Qualitative Case Study for University X (UX) - Alzmeter, Laura (GILE Journal of Skills Development, 2025)
This study paper explores the student participation in the life and governance of Hungarian higher education institutions with a focus on University X (an anonymised institution). It aims to answer two questions in regard to the key factors influencing the students’ participation and the differences that emerge between the Hungarian and the international students at University X. As higher education becomes more diverse and internationalised, understanding how students from different backgrounds engage with institutional governance is crucial for promoting inclusive and integrative practices. Using a qualitative case study design, this paper involved semi-structured interviews with five participants from University X: two staff members from two different international offices, two student representatives (one representing the Bachelor and Master students’ union, and another one representing the doctoral student union), and one international student representative. These interviews provided insights into both formal and informal mechanisms of student participation in the university life or the university governance, the opportunities offered, and the students’ challenges in influencing policies and institutional practices. The analysis revealed that the key factors influencing the students’ participation are connected to the effective communication, the inclusive environment, the support systems, the different available events, the collaboration between the administration and the student bodies, and the feedback mechanisms. Alternatively, differences arise between Hungarian and international students due to language, cultural and social integration, student representation and decision-making, and information access. This study concludes that fostering great student participation requires not only structural changes but also cultural adaptation and institutional efforts to ensure all students have equitable opportunities.